PENERAPAN DIGITAL MARKETING DAN BRANDING PRODUK PADA KOPERASI TENUN PANDAI SIKEK DI KECAMATAN X KOTO KABUPATEN TANAH DATAR - Rahmi Eka Putri; Laela Susdiani; Ricky Akbar (LPPM Universitas Andalas, 2021)
This Community Service activity is carried out at the Pandai Sikek Weaving Cooperative located in Nagari Pandai Sikek, X Koto District, Tanah Datar Regency. This activity aims to provide assistance in managing digital marketing and product branding at the Pandai Sikek Weaving Cooperative to members of the cooperative who are weavers from Nagari Pandai Sikek. Products are marketed in the form of woven cloth typical of Pandai Sikek and some handicrafts typical of West Sumatra. The Pandai Sikek Weaving Cooperative currently does not have a name and logo for the product being marketed, so the product does not have an identity that can be recognized by the public. The method used in this activity is brainstorming with activity partners to obtain the same thoughts about product names and logos. In addition, the implementation method is also in the form of training and assistance in managing digital marketing as one of the product marketing strategies. In this activity, product branding has been produced with the name